DIALOGUE AND DEVELOPMENT: IMPROVING VIDEO FEEDBACK ASSESSMENT - Leon Townsend-Nakai; Craig Gamble (PUPIL: International Journal of Teaching, Education and Learning, 2026)
Feedback is a vital part of language teaching, yet learners often develop negative feelings toward it. In Japanese classrooms, where instruction is typically teacher-centered, differences in interpreting evaluation criteria can reduce engagement and limit progress. To address these challenges, alternative methods such as technology-enhanced video feedback have been explored, offering interactive and dialogical advantages over traditional approaches. This shift reflects growing recognition of the role of dialogue in fostering learner knowledge and critical thinking. This study investigates how dialogical approaches within video feedback can strengthen the teaching and learning process. Findings suggest that video assessment encourages learners to engage more actively with feedback while also enhancing its multimodal qualities. Initial results indicate that learners respond positively to this form of feedback, highlighting its potential to promote stronger teacher–student dialogue, increase engagement, and improve overall learning outcomes.